Phyllochron and Leaf area ratio of maize influenced by different nitrogen levels and Growing Degree Days in two different climatic conditions - Mohammed, Aram Abbas (Sulaimani Journal for Pure and Applied Sciences, 2019)
The present study shows the response of maize hybrids to different thermal time conditions with different nitrogen levels, the investigation comprises two different field experiments were conducted in the Qlyasan Research Center\ University of Sulaimani during the spring and autumn seasons in 2017. The experiments were arranged as a split-plot design with three replications. Three different nitrogen levels involved in the main plots and four maize hybrids were cultivated in the sub-plots. In addition to the Phyllochron, the Plant leaf area, and accumulated dry matter were studied in different growth stages for estimating the leaf area ratio of the four maize hybrids. The results manifested efficient impact of thermal time on the studied traits in comparing to nitrogen fertilization, there was a fundamental effect of thermal time expressed as accumulated growing degree days (GDD) on the physiological and biochemical processes of growth and development of maize hybrids. The accumulated GDD from seeding to 50% tasseling was 1050.9 calculated in 58.5 DAS in autumn, whereas in spring season the accumulated GDDs was 1367.6 estimated in 66.25 DAS. Whilst, the linear increases in the leaf appearance and shorter phyllochron manifested in the autumn season, the maximum value of study criteria was not obtained with maximum nitrogen application in all cases. There was a linear decline of the value of LAR across the growth stages from V4-V5 to R3 which was underlined with regression value of r2 of 0.99 , 0.98, and 0.92 for nitrogen levels (N1,N2, and N3) respectively. The rate of LAR in autumn season was not similar to the previous season, the maximum value of LAR was shown with the effect of second level N2 in vegetative growth V8-V10 and reproductive growth stage R3 with first level N1 revealing curvilinear regression.
Keywords: Leaf appearance; Crop heat Unit; Corn; leaf longevity